INCIDENCE AND FACTORS FOR MATERNAL SATISFACTION AFTER CAESAREAN SECTION: A CROSS-SECTIONAL STUDY: a cross-sectional study - Ikram, Mobeen; Mahboob, Saira; Zaineb, Sadia (Pakistan Armed Forces Medical Journal, 2020)
Objective: To evaluate the factors for perioperative patient satisfaction in parturient undergoing lower section cesarean section, with a view assess anesthesia quality. Study design: cross sectional, analytical study Place and Duration of study: Department of Anesthesiology and Gynecology & Obstetrics, Combined Military Hospital, Okara Cantt for 04 months from January to April 2019. Material and method: A total of 400 parturient undergoing cesarean section were included in our study. The patients were given a questionnaire to fill on discharge. Our outcomes were frequency of patient satisfaction and various factors affecting it. SPSS version 20 was used to analyze data. Mean ± SD was described for quantitative variables and frequency (percentage) for qualitative variables. T-test and chi square used to analyze significance. p-value ≤0.05 taken as significant. Results: A total of 400 questionnaires were assessed in final analysis. The overall patient satisfaction was 382 (95.5%) with 4 (1%) showing dissatisfaction; whereas 14 (3.5%) didn’t answer this question. 395 (98.8%) underwent LSCS under spinal anesthesia. There wasno difference in patient satisfaction in regards to intra-operative concern alleviation, discomfort, previous number of LSCS, parturient age, choice of anesthesia; p value > 0.05. There was higher dissatisfaction in patients who experienced post-operative complaints, most notably pain; p=0.000. Patient satisfaction was higher in mothers who experienced joy on hearing their newborns cries; p=0.000 Conclusion: The overall patient satisfaction in our study was high and only few factors causing patient dissatisfaction which included postoperative complaints most notably pain.